Establishing children's library in a mall and non-mall setting a case study of the Children's library and Museo Pambata Resource Center - Taruc, Leira Leonor S.; Yang, Jackson V. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2001)
A full-scale study between two children's libraries in a mall and non-mall setting was undertaken, one is The Children's Library at the Robinsons Galleria mall in Quezon City and the other is the Museo Pambata Resource Center in Manila. Various aspects of two libraries (i. e. staff, facilities, collection, and activities for children and demographic characteristics for children) were examined for comparison.
Data collected from The Children's Library included the subjects and size of the collection, the activities for children for the month of November to January, facilities, staff and their employment status as professional or non-professional, statistics of users according to time, day and type of patron, key card application based on the type of school and patron, in-library use of materials, and the demographic characteristics of children visiting the library.
On the other hand, documents from Museo Pambata Resource Center like the accession record for the year 1996-2000, membership application as of April 2000-present and calendar of activities for children were analyzed. Interview with the librarian was conducted in gathering data about the staff and facilities. Questionnaires were randomly distributed to the children clientele of the Resource Center.
The principal findings of the study show that there is an emphasis in the subject Literature in the collection of the two libraries. The activities offered for children are more diverse in The Children's Library as compared to the Museo Pambata Resource having only 2 regular activities per week.
Furthermore, the Resource Center is understaffed as opposed to The Children's Library. In consequence data like the statistics of daily users, in-library use of materials are not available. The most frequent age of respondents of both libraries is between 6-7 years old. Majority of the children who visit the library are female. Certain characteristics of the respondents like their companion in going to the library and the degree of influence they exhibit vary between the two libraries.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Children's libraries -- Philippines; Children's Library (Robinsons Galeria, Quezon City).; Museo Pambata Resource Center (Manila).